A Review on Online Analytical Process - Hamidi, Mohammad Salem; Rahman, Hasib (E-COMMERCE FOR FUTURE & TRENDS, 2022)
Innovation is a critical component of any modern business's competitiveness. This study presents the systematized findings of an investigation into OLAP technology. Nowadays, OLAP is one of the most widely used technologies in the world, with the majority of enterprise organizations utilizing the OLAP system for business analysis and decision support. In this review, we used a data collection method and a document review. As OLAP and data warehouse technology mature, an important goal is to perform some processing and analysis of enterprise data, thereby providing better, faster, and more efficient support, in order to provide enterprises with a greater competitive advantage. As a result, OLAP and data warehouse technology are gradually becoming the first choice for the majority of organizations. The development of a business-oriented financial analysis system provides a good solution to the problems encountered in the work of corporate financial analysis because of the support of these two technologies.